miRNA-124 prevents rat diabetic retinopathy by inhibiting the microglial inflammatory response - Chen, Ying; Schlotterer, Andrea; Kurowski, Luke; Li, Lin; Dannehl, Marcus; Hammes, Hans-Peter; Lin, Jihong (International journal of molecular sciences, 2023)
Diabetic retinopathy (DR) is characterized by vasoregression and glial activation. miRNA-124 (miR-124) reduces retinal microglial activation and alleviates vasoregression in a neurodegenerative rat model. Our aim was to determine whether miR-124 affects vascular and neural damage in the early diabetic retina. Diabetes was induced in 8-week-old Wistar rats by streptozotocin (STZ) injection. At 16 and 20 weeks, the diabetic rats were intravitreally injected with miR-124 mimic, and retinae were analyzed at 24 weeks. Microvascular damage was identified by evaluating pericyte loss and acellular capillary (AC) formation. Müller glial activation was assessed by glial fibrillary acidic protein (GFAP) immunofluorescence staining. Microglial activation was determined by immunofluorescent staining of ionized calcium-binding adaptor molecule 1 (Iba1) in whole mount retinae. The neuroretinal function was assessed by electroretinography. The expression of inflammation-associated genes was evaluated by qRT-PCR. A wound healing assay was performed to quantitate the mobility of microglial cells. The results showed that miR-124 treatment alleviated diabetic vasoregression by reducing AC formation and pericyte loss. miR-124 blunted Müller glial- and microglial activation in diabetic retinae and ameliorated neuroretinal function. The retinal expression of inflammatory factors including Tnf-α, Il-1β, Cd74, Ccl2, Ccl3, Vcam1, Tgf-β1, Arg1, and Il-10 was reduced by miR-124 administration. The elevated mobility of microglia upon high glucose exposure was normalized by miR-124. The expression of the transcription factor PU.1 and lipid raft protein Flot1 was downregulated by miR-124. In rat DR, miR-124 prevents vasoregression and glial activation, improves neuroretinal function, and modulates microglial activation and inflammatory responses.
Gesehen am 15.10.2024